2022
DOI: 10.35808/ijeba/773
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Risk Model to Identify Factors that Affect Students’ Critical Achievement in Remote Lab Courses

Abstract: Purpose:The research objective is to address the problem of students' critical achievement in remote lab courses aiming at identifying the risk factors of students' failure by exploiting e-learning learning analytics. A robust risk model is developed to serve this purpose. The research is orented into NI-Elvis remote lab courses given that they offer a stable environment in the context of which automation lab courses could be effectively delivered. Design/methodology/approach: A robust risk model was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 24 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…In the case of NI-ELVIS remote labs, one study has proved that the student's interaction with the NI-ELVIS LMS strongly predicts students' critical performance. The same study has pointed out that the activities' completion concerning the theoretical material and the theoretical exercises significantly affect students' outcomes [31]. As the studies mentioned above underline, no specific set of factors affects students' critical performance in any course.…”
Section: Predicting Students At Risk In Remote Labsmentioning
confidence: 91%
See 4 more Smart Citations
“…In the case of NI-ELVIS remote labs, one study has proved that the student's interaction with the NI-ELVIS LMS strongly predicts students' critical performance. The same study has pointed out that the activities' completion concerning the theoretical material and the theoretical exercises significantly affect students' outcomes [31]. As the studies mentioned above underline, no specific set of factors affects students' critical performance in any course.…”
Section: Predicting Students At Risk In Remote Labsmentioning
confidence: 91%
“…Many studies indicate e-learning platforms' vital role in predicting at-risk students [25][26][27][28][29][30][31]. Previous studies have also indicated that a proper analysis of students' behavioral engagement could lead to developing competent risk models and generating respective prediction models.…”
Section: Predicting Students At Risk In Remote Labsmentioning
confidence: 99%
See 3 more Smart Citations